2000
DOI: 10.1074/jbc.m000253200
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi Surface Mucins with Exposed Variant Epitopes

Abstract: The protozoan parasite Trypanosoma cruzi, the agent of Chagas disease, has a large number of mucin molecules on its surface, whose expression is regulated during the life cycle. These mucins are the main acceptors of sialic acid, a monosaccharide that is required by the parasite to infect and survive in the mammalian host. A large mucin-like gene family named TcMUC containing about 500 members has been identified previously in T. cruzi. TcMUC can be divided into two subfamilies according to the presence or abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 55 publications
2
39
0
3
Order By: Relevance
“…Antibodies recognizing the parasite mucins (Pollevick et al 2000) and those neutralizing the trans-sialidase activity have been found in sera from T. cruzi infected humans and animals (Leguizamón et al 1994a, b). Therefore, we can speculate that cross-reactive antibodies induced by the homologous mucins and sialidases expressed in T. rangeli might be involved in the protective effect of T. rangeli infection on evolution of Chagas disease.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies recognizing the parasite mucins (Pollevick et al 2000) and those neutralizing the trans-sialidase activity have been found in sera from T. cruzi infected humans and animals (Leguizamón et al 1994a, b). Therefore, we can speculate that cross-reactive antibodies induced by the homologous mucins and sialidases expressed in T. rangeli might be involved in the protective effect of T. rangeli infection on evolution of Chagas disease.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably much of this surface sLe x occurs on MUC1 because it is overexpressed in wild-type MARY-X but undoubtedly other sialylated surface molecules are also fucosylated by these two approaches. 24,25 FucT-III transfection was . SLe x/a -MARY-X exhibits a similar enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…Tetramethylrhodamine B isothiocyanate-conjugated anti-mouse antibody (Sigma) was used at 1:400 and fluorescein isothiocyanate-conjugated anti-rabbit antibody (Sigma) at 1:2000. (Pollevick et al, 2000).…”
Section: Western Blot Analysis and Immunofluorescencementioning
confidence: 99%
“…To investigate whether the free GPI is exposed on the surface of the null mutant, living procyclic forms were incubated in serum-free medium, resulting in the removal of sialic acid residues by the endogenous trans-sialidase (Pollevick et al, 2000). The cells were subsequently treated with galactose oxidase and the oxidized terminal ␤-galactose residues were reduced with [ 3 H]borohydride.…”
Section: Free Gpis Are Exposed On the Surface Of The Null Mutantmentioning
confidence: 99%